Pengenalan Apotek Hidup sebagai Edukasi Kesehatan Sejak Dini pada Siswa SD Negeri 01 Gelam - Veti Barokah; Gina Zahra; Reva Sila Kinaya; Dadan Maulana Yusuf (INDO PUBLISHING, 2025)
The apotek hidup (living pharmacy) concept refers to utilizing available land to grow medicinal plants (TOGA) that provide both health benefits and educational value. This study was motivated by the importance of instilling health knowledge based on local wisdom at an early age for elementary school students. SD Negeri Gelam 01 was chosen as the research site due to its spacious open area suitable for developing a school medicinal plant garden, which had not been optimally utilized for educational purposes. This research employed a Participatory Action Research (PAR) approach, engaging 30 fourth and fifth-grade students actively in all stages, from material delivery, planting practice, to plant maintenance. Data were collected through observation sheets, knowledge questionnaires, and interviews with supervising teachers. Quantitative data were analyzed using the gain score method to measure knowledge improvement, while qualitative data were analyzed descriptively based on observations and interviews. The results indicate a significant increase in students’ knowledge of medicinal plants, from an average of 1–2 types to 4–5 types after the activity. Additionally, students’ practical planting skills and environmental awareness improved considerably. The apotek hidup program proved effective in integrating health education, gardening skills, and environmental awareness character building in elementary school students.